'Just like breathing': A portrait of an 85-year-old veteran teacher. Issue 6 (18th August 2021) - Gray, Christina; Lowe, Geoffrey M.; Prout, Peter F.; Jefferson, Sarah
ABSTRACT: Through a phenomenological lens of portraiture methodology, this article explores the career experiences of a veteran acting teacher who, at the age of 85 years, remains highly passionate and dedicated to his work with younger aspiring actors. The article reveals how for this veteran teacher, his strong teacher identity characterised by a quest for challenge and a commitment to career-long professional development are significant to maintaining relevance and passion for teaching. As many countries grapple with issues surrounding the retention of veteran teachers, understanding the ways in which he maintains his passion and commitment over succumbing to stress and burn out like so many teachers in the performing arts is timely.